Circuit Synthesis through Combination of Evolutionary and Swarm Algorithms - Reis, Cecília (2019)
Evolutionary Computation (EC) is a growing research field of Artificial Intelligence (AI), particularly of Computational Intelligence (CI). EC is the general term for several computational techniques which use ideas and get inspiration from natural evolution/adaptation and is divided in two main areas: the Evolutionary Algorithms (EA) and the Swarm Intelligence (SI). This paper presents hybridization between an EA algorithm - the Genetic Algorithm (GA) and a SI algorithm - the Particle Swarm Optimization Algorithm (PSO). The resulting algorithm is applied to the synthesis of combinational logic circuits. With this combination is possible to take advantage of the best features of each particular algorithm.